Borehole seismoelectric logging using a shear-wave source: Possible application to CO2 disposal?. (February 2015) - Zyserman, Fabio I.; Jouniaux, Laurence; Warden, Sheldon; Garambois, Stéphane
Abstract : Highlights: We modify Pride's equations to take into account partial CO2 saturations. In our models we employ shear-wave sources in surface-to-borehole geometries. Seismoelectric responses are sensitive to a wide range of CO2 saturations. Abstract: The behaviour of CO2 deposition sites – and their surroundings – during and after carbon dioxide injection has been matter of study for several years, and several geophysical prospection techniques like surface and crosshole seismics, geoelectrics, controlled source electromagnetics among others, have been applied to characterize the behaviour of the gas in the reservoirs. Until now, Seismolectromagnetic wave conversions occurring in poroelastic media via electrokinetic coupling have not been tested for this purpose. In this work, by means of numerical experiments using Pride's equations – extended to deal with partial saturations – we show that the seismoelectric and seismomagnetic interface responses (IR) generated at boundaries of a layer containing carbon dioxide are sensitive to its CO2 content. Further, modeling shear wave sources in surface to borehole seismoelectric layouts and employing two different models for the saturation dependence of the electrokinetic coefficient, we observe that the IR are sensitive to CO2 saturations ranging between 10% and 90%, and that the CO2 saturation at which the IR maxima are reached depends on the aforementioned models. Moreover, the IR are still sensitive to different CO2 saturations for a sealed CO2 reservoir covered by a clay layer. These results, which should be complemented by the analysis of the IR absolute amplitude, could lead, once confirmed on the field, to a new monitoring tool complementing existing ones.